FRI0372 Factors Associated with Persistent Fatigue in Patients with RA or AXSPA with Low Disease Activity Under Biological DMARDS. (9th June 2015) - Nizeica, V.; Normand, M.; Pallot-Prades, B.; Collet, P.; Locrelle, H.; Amouzougan, A.; Thomas, T.; Marotte, H.
Abstract : Background: Patients with chronic inflammatory rheumatism claim fatigue as a key symptom of their disease. The association between fatigue and inflammatory joint diseases such as rheumatoid arthritis (RA) or axial spondyloarthritis (axSpA) has been considered so far to be mainly related to disease activity. However, many arthritic patients despite having a low disease activity under a bDMARD still report severe fatigue with a poor quality of life and there is no specific treatment of fatigue in those RA and axSpA patients. Objectives: The main objective of our study was to investigate the mechanisms of this persistent fatigue by exploring factors associated with fatigue in RA or axSpA patients in low disease activity under bDMARDs treatment. Methods: Arthritic patients with low disease activity (DAS28<3.2 for RA or BASDAI<4/10 and ASDAS<2.1 for axSpA) were enrolled in a monocentric observational and cross-sectional study. All patients were treated with a bDMARD associated or not with conventional synthetic (cs)DMARD. All patients were successively enrolled in this study. Demographic, clinical and biological patient characteristics were recorded. Fatigue was assessed by a validated self-questionnaire FACIT-F and by VAS for fatigue. Anxiety and depression were estimated by HAD scores. Physical activity was assessed by a validated score IPAQ-SF. Sleep quality was assessed using the number of nighttime awakenings and the PSQI score. Function disability was evaluated with HAQ. Results: One hundred patients were included in the study with 55 RA (86% female) and 45 axSpA (68% men), with a mean disease duration of 11.9±7.9 years. Furthermore, higher levels of physical activity together with lower functional disabilities were observed in axSpA patients compared to RA patients (Table 1 ). Notably, fatigue level was similar in RA and axSpA patients. After the univariate statistical analysis, 7 parameters were statistically correlated with FACIT-F in our whole population: age, gender, sleep quality (PSQI and number of nighttime awakenings), anxiety (HAD anxiety), depression (HAD depression), and functional disability (HAQ). Four parameters remained positively associated with fatigue in the multiple linear regression: age, sleep quality (number of nighttime awakenings), depression (HAD depression), and functional disability (HAQ). Similar results were obtained when adding arthritic disease type (either RA or axSpA) in the multivariate analysis. Further analyses using ANCOVA test identified higher association between handicap and fatigue in axSpA patients than in RA patients. Fatigue level increased with higher handicap (p<0.001) and this trend was stronger in axSpA patients (p<0.05). Fatigue also increased with higher depression (p<0.001), with higher age (p<0.05) but the strength of these associations was similar in both RA and axSpA patients. Conclusions: Our study suggests the importance of advance care of depression, sleep quality and functional deficit in patients with low-activity RA or axSpA in order to improve their state of fatigue and consequently to increase their quality of life. Disclosure of Interest: None declared